The rule of law for marine environmental governance in maritime transport: China’s experience - Xing, Houqun; Cao, Xingguo; Su, Zixiu (Frontiers in Marine Science, 2022)
Maritime transport is a major source of pollution of marine environment, which is the essential object in a series of international maritime legislations and various countries’ domestic laws. Focused on protecting the marine environment, China has spent over 40 years developing the rule of law for marine environmental governance in maritime transport, including efforts made in legislation, law enforcement, and the judiciary. In this article, we attempt to examine China’s experience and practice in the marine environment, explain the logic and consideration in relevant practices, and summarize China’s paradigm for the rule of law for such governance. China has sought to resolve two major issues: the relationship between domestic and international law and the balance of interests between flag, coastal, and port states, offering a vivid model of marine environmental governance on which other countries can base their own legal systems. The findings reveal that with following and enforcing the international law of the sea, now China’s domestic laws have form lawful authority on binding foreign vessels. China is continually strengthening the construction of its legislative system to harmonize inconsistencies and keep pace with international marine environmental law. To eliminate administrative inefficiency resulting from cumbersome procedures, China has reformed its maritime enforcement system by consolidating multiple administrations. China’s independent maritime judicial system is meeting the demand to develop environmental specialization, enabling further exploitation of its profession in solving maritime environment cases and implementing environmental legislation.